Highly selective vapochromic fluorescence of polycarbonate films Doped with an ICT‐Based solvatochromic probe. Issue 15 (5th May 2017) - Ahmad, Muzaffer; Platonova, Irina; Battisti, Antonella; Minei, Pierpaolo; Brancato, Giuseppe; Pucci, Andrea
ABSTRACT: The vapochromic properties of a fluorescent 3‐[2‐(4‐nitrophenyl) ethenyl]‐1‐(2‐ethylhexyl)‐2‐methylindole (NPEMI‐E) characterized by intramolecular charge transfer (ICT) character, dispersed in polycarbonate (PC) films is reported. NPEMI‐E solvatochromism is investigated by means of experimental and computational methods. Fluorescent PC films containing 0.1 wt % of NPEMI‐E are prepared and exposed to saturated atmospheres of different volatile organic compounds (VOCs). NPEMI‐E/PC films show remarkable and reversible vapochromism when exposed to VOCs with high polarity index and favorable interaction with PC matrix such as CHCl3 . Only minor variations in the emission wavelength are actually recorded for all other classes of VOCs investigated. The hue parameter is also used for the effective extraction of spectral information from digital color images without the need for wavelength discriminators. Overall, the present results support the use of NPEMI‐E/PC films for the cost‐effective detection of CHCl3 vapors. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1171–1180 Abstract : Solvatochromic indole fluorophores characterized by intramolecular charge transfer (ICT) character endow polycarbonate (PC) films with vapochromic features once exposed to saturated atmospheres of different volatile organic compounds (VOCs). The thin films show remarkable and reversible vapochromism when exposed to VOCs with high polarity index such as CHCl3 and favorable interaction with the PC matrix. The vapochromism is also effectively quantified by the very simple and inexpensive hue determination method.